Longitudinal evaluation of biomechanical indices in fellow eyes of patients with keratoconus classified as having very asymmetric ectasia with normal topography - Kovalchuk, Bogdana; Khoramnia, Ramin; Son, Hyeck Soo; Meis, Jan; Winkler, Philip; Naujokaitis, Tadas; Köppe, Maximilian; Auffarth, Gerd U.; Augustin, Victor A. (Journal of refractive surgery, 2024)
PURPOSE: To evaluate the biomechanical longitudinal variability and progression of tomographically normal fellow eyes of patients with keratoconus. - METHODS: - Of 513 patients with keratoconus, 30 patients with tomographically normal fellow eyes were included in this study. Tomographic and biomechanical parameters of the Pentacam and Corvis ST (Oculus Optikgeräte GmbH) were analyzed in multiple follow-up examinations, including the ABCD grading, Belin/Ambrósio Enhanced Ectasia total deviation index (BAD-D), Corvis Biomechanical Index (CBI), Corvis Biomechanical Factor (CBiF), and Tomographic and Biomechanical Index (TBI). A mixed regression model was applied. The results were compared to a healthy control group (n = 17) and a keratoconus group (n = 20). - RESULTS: - Within a maximum observation period of 3.3 years, no fellow eye (0%) showed a progression to tomographically evident keratoconus. No significant change in tomographic or biomechanical parameters was detected over the study period. The indices BAD-D, CBI, CbiF, and TBI exhibited a certain variability over time, whereas the tomographic ABC parameters and maximum keratometry barely changed. This was also shown in the control group and for all parameters in the keratoconus group, except the TBI. - CONCLUSIONS: - During the observation period none of the normal fellow eyes progressed to tomographically detectable keratoconus. However, biomechanical parameters CBI, CbiF, and TBI showed pathological values in 43.3% of eyes and certain variability. Subsequent studies with a longer observation period are warranted to confirm the biomechanical trends seen in this study and to rate the ability of single measurements to diagnose early keratoconus